Pit nucleation on as-cast aluminiuim alloy AW-5083 in 0.01M NaCl - Dolić N.; Malina J.; Begić-Hadžipašić A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The use of aluminium alloys in a wide range of technical applications is related mostly to the two facts: they facilitate weight saving of final products (if compared to the steel) and they are prone to spontaneous passivity due to the coherent surface oxide layer which impedes further reaction of aluminium with the environment. Among the commercial Al alloys, EN AW-5083 alloy is a representative non-heat treatable Al-Mg based alloy which possesses many interesting characteristics as a structural material, such as low price, moderately high strength, high formability in conjunction with superplasticity and good corrosion resistance in marine atmospheres. Aiming to enhance the knowledge of possible interactions of studied alloy EN AW-5083 in as-cast condition with chloride media, electrochemical measurements were used to follow the pitting behaviour in 0.01 M NaCl. The results of tests have shown that susceptibility of alloy to pitting corrosion is strongly influenced by the microstructural constituents of the alloy in as-cast condition.